Effects of Honey on Oral Mucositis among Pediatric Cancer Patients Undergoing Chemo/Radiotherapy Treatment at King Abdulaziz University Hospital in Jeddah, Kingdom of Saudi Arabia. (7th February 2017) - Al Jaouni, Soad K.; Al Muhayawi, Mohammad S.; Hussein, Abear; Elfiki, Iman; Al-Raddadi, Rajaa; Al Muhayawi, Saad M.; Almasaudi, Saad; Kamal, Mohammad Amjad; Harakeh, Steve
Abstract : One of the most common complications of cancer chemotherapy is oral mucositis. This study evaluates the therapeutic effects of honey with the focus on grade III and IV oral mucositis, reduction of bacterial and fungal infections, duration of episodes of oral mucositis, and body weight in pediatric leukemic patients undergoing chemo/radiotherapy. This is an open labeled randomized controlled study conducted at our hospital on 40 pediatric cancer patients undergoing chemo/radiotherapy. All the 40 patients included in this study experienced a sum total of 390 episodes of fever and neutropenia associated with oral mucositis. A significant reduction of oral mucositis, associated Candida, and aerobic pathogenic bacterial infections was noted in patients in the honey treatment group. Also, there is a significant decrease in the duration of hospitalization for all those in the treatment group combined with a significant increase of body weight, delayed onset, and decreased severity of pain related to oral mucositis. Complications of oral mucositis can be tremendously reduced by the topical application of local Saudi honey and honey should be used as an integrative approach in prophylaxis and treatment of chemo/radiotherapy-induced oral mucositis in pediatric cancer patients. Further research is needed to elucidate and better understand the underlying mechanism.